Natural Radioactivity in Some Food Crops from Bangka-Belitung Islands, Indonesia - Syarbaini Syarbaini; A. Warsona; D. Iskandar (Atom Indonesia, 2014)
Natural radioactivities of food crops are the main sources of internal radiation exposure in humans. Bangka-Belitung islands of Indonesia has a higher natural background radioactivity than typical areas because of tin mining activities.The study was carried out to evaluate the natural radioactivity concentration in several food crops grown in Bangka and Belitung Islands. Food samples collected from Bangka and Belitung Islands were analyzed by means of a gamma spectroscopy for natural radionuclides 226Ra, 232Th and 40K. The annual intake of the food was estimated on the basis of their average annual consumption. Calculations were also made to determine the effective dose to an individual consuming such diets. The intakes of these radionuclides were calculated using the concentrations in Bangka-Belitung foods and annual consumption rates of these food. Annual intakes of these radionuclides were as follows: 226Ra = 190.00; 232Th = 633.79 and 40K = 2065.10 Bq/year. The annual internal dose resulting from ingestion of radionuclides in food was 0.205 mSv/year which is much lower than annual dose limit of 1 mSv for general public. The radionuclides with highest consumption is 40K followed by 232Th and 226Ra.Received: 21 October 2013; Revised: 22 April 2014; Accepted: 28 April 2014